COVID-19 vaccine uptake at six months post vaccine availability in Central Texas: an observational study disentangling the moveable middle - Litaker, John R.; Lopez Bray, Carlos; Tamez, Naomi; Durkalski, Wesley; Taylor, Richard (Frontiers in Health Services, 2025)
BackgroundVaccine hesitancy is a multifactorial construct that posits vaccine uptake is based on person, place, time, and vaccine type. This study sought to identify individuals at about the six-month mark of COVID-19 vaccine availability in Central Texas to determine if they were vaccine acceptors, vaccine refusers, or in the moveable middle using the COVID-19 Vaccination Uptake Behavioral Science Task Force framework developed for the US Centers for Medicare and Medicaid Services and to disentangle individuals in the moveable middle to either vaccine acceptors or vaccine refusers.MethodsAn online survey was distributed to individuals with Affordable Care Act insurance to assess: (1) COVID-19 vaccine uptake; and (2) plans to obtain a COVID-19 vaccine for those who had not yet received at least one dose of a COVID-19 vaccine. The study period was June 27, 2021, through July 13, 2021. Quantitative and qualitative data were collected.Results900 individuals participated in this study. The point prevalence of COVID-19 vaccine acceptance and refusal was 94.9% (n = 854) and 5.1% (n = 46), respectively. For those who were initially identified in the moveable middle, 84.6% exited the moveable middle as vaccine refusers. Black or African American race (p < 0.001), income level (p = 0.004), and education level (p = 0.015) were associated with obtaining at least one dose of the COVID-19 vaccine.ConclusionsReal-world evidence at the time of a public health emergency can be used to determine point prevalence of vaccine uptake to stratify individuals as vaccine acceptors, vaccine refusers, or the moveable middle. Such evidence can be used to support health policy and planning during a public health emergency.